A novel time-domain fitting method for estimating Fricke-Morse model parameters based on single-frequency sinusoidal complete response measurements. (1st September 2022) - Zhang, F.; Liu, F.; Zhong, H.; Li, J.; Lin, H.; Yang, Y.
Abstract: Fricke-Morse model is a widely-used 2R-1C equivalent circuit for electrical bioimpedance (EBI) analysis, whose model parameters are usually fitted in multi-frequency (MF) EBI measurements. This paper proposes a novel time-domain fitting method on estimation of the model parameters in single-frequency (SF) sinusoidal complete response (SCR) (the combination of initial transient and steady-state response) measurements. The analytical expressions of the model parameters are firstly deduced based on SCR analysis. Then a time-domain least square iterative optimization algorithm is developed to fit the model parameters, in which the analytical model expressions are calculated as the iterative initial values. Experimental measurements conducted on a 2R-1C circuit and the biceps brachii of a healthy volunteer in SF-SCR measurements show the mean difference less than 1% and 5%, respectively, compared to the results estimated using a commercial EBI device in reference MF-EBI measurements. The proposed SF-SCR method provides an alternative to EBI analysis, which could greatly simplify the hardware design and thus significantly reduce the equipment cost compared to the traditional MF-EBI method.